HDL particle number and size as predictors of cardiovascular disease - Kontush, Anatol (Frontiers in Pharmacology, 2015)
Previous studies indicate that reduced concentrations of circulating high-density lipoprotein (HDL) particles can be superior to HDL-cholesterol (HDL-C) levels as a predictor of cardiovascular disease. Measurements of HDL particle numbers, therefore, bear a potential for the improved assessment of cardiovascular risk. Furthermore, such measurement can be relevant for the evaluation of novel therapeutic approaches targeting HDL. Modern in-depth analyses of HDL particle profile may further improve evaluation of cardiovascular risk. Although clinical relevance of circulating concentrations of HDL subpopulations to cardiovascular disease remains controversial, the negative relationship between the number of large HDL particles and cardiovascular disease suggests that assessment of HDL particle profile can be clinically useful. Reduced mean HDL size is equally associated with cardiovascular disease in large-scale clinical studies. Since HDL-C is primarily carried in the circulation by large, lipid-rich HDL particles, the inverse relationship between HDL size and cardiovascular risk can be secondary to those established for plasma levels of HDL particles, HDL-C, and large HDL. The epidemiological data thereby suggest that HDL particle number may represent a more relevant therapeutic target as compared to HDL-C.